Bobon Santoso's Digital Communication Strategy for Building Personal Branding through "Kuali Merah Putih" YouTube Content - Alfin Ardiansyah; R. Ayu Erni Jusnita; Nurul Suhesti (Jurnal Multidisiplin West Science, 2026)
The rapid growth of digital media has increased the importance of personal branding among content creators. This study examines how Bobon Santoso employs digital communication strategies to build personal branding through the “Kuali Merah Putih” YouTube content series. The study analyzes visual, narrative, performative, symbolic, and interactive elements contributing to identity construction. Using a qualitative case study approach, data were collected from 12 purposively selected YouTube videos through non-participant observation, digital documentation, and thematic analysis. The findings reveal that Bobon Santoso’s personal branding is constructed through consistent visual identity, large-scale cooking spectacles, nationalist symbolism, social storytelling, performative authenticity, and audience engagement. The “Merah Putih” symbol reinforces nationalism, solidarity, and social responsibility, while authentic performances and humanitarian narratives foster parasocial relationships, audience loyalty, emotional attachment, and trust. Effective personal branding extends beyond visibility by integrating meaningful social values and sustained audience interaction.